PERFECT HUMAN INTERPRETATION IN ALISHER NAVOY’S CREATION - Ortiqova Gulbahor Kamol qizi; M.A. Omanova (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines the interpretation of the perfect man in the works of Alisher Navoi. The educational aspects of the works "Mahbub ul Qulub" and "Munshaot" are highlighted.